2022
DOI: 10.1001/jamasurg.2022.1298
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hepatic Arterial Infusion Pump Chemotherapy vs Resection for Patients With Multifocal Intrahepatic Cholangiocarcinoma

Abstract: IMPORTANCE Intrahepatic cholangiocarcinoma (iCCA) is often multifocal (ie, satellites or intrahepatic metastases) at presentation. OBJECTIVE To compare the overall survival (OS) of patients with multifocal iCCA after hepatic arterial infusion pump (HAIP) floxuridine chemotherapy vs resection. DESIGN, SETTING, AND PARTICIPANTSIn this cohort study, patients with histologically confirmed, multifocal iCCA were eligible. The HAIP group consisted of consecutive patients from a single center who underwent HAIP floxur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…To the Editor We read the study by Franssen et al with great interest. The authors showed that the overall survival after hepatic arterial infusion pump (HAIP) floxuridine chemotherapy in patients with multifocal intrahepatic cholangiocarcinoma was comparable with that in patients who underwent resection and confirmed the results of a previous study .…”
mentioning
confidence: 66%
“…To the Editor We read the study by Franssen et al with great interest. The authors showed that the overall survival after hepatic arterial infusion pump (HAIP) floxuridine chemotherapy in patients with multifocal intrahepatic cholangiocarcinoma was comparable with that in patients who underwent resection and confirmed the results of a previous study .…”
mentioning
confidence: 66%
“…In addition, several guidelines also recommend palliative chemotherapy for bi-or multifocal ICC (39,40). However, a recent cohort study reported similar long-term efficacy of surgical resection and chemotherapy for multifocal ICC, and a metaanalysis suggested that re-operation may partly improve the short-term and long-term outcomes of patients with recurrent ICC (41,42). At present, open hepatectomy is the most common surgical method used for the treatment of ICC.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, elimination of accumulated detrimental senescence and induction of acute cellular senescence might be an important direction, and more studies on the interaction between cellular senescence and antitumor microenvironment are warranted. Noticeably, the remaining three compounds have also been reported to have antitumor capability, although their correlation with cellular senescence has not been characterized (77)(78)(79). In consideration of the complicated involved pathways in cellular senescence (4,(52)(53)(54)(55), we permuted additional candidate compounds, including cell-cycle inhibitors, bromodomain and BET inhibitors, PI3K-AKT pathway inhibitors, and multikinase inhibitors, and the TIS-high group exhibited a higher susceptibility to these drugs.…”
Section: Discussionmentioning
confidence: 99%